Laminar and Cellular Distribution of Monoamine Receptors in Rat Medial Prefrontal Cortex - Santana, Noemí; Artigas, Francesc (Frontiers in Neuroanatomy, 2017)
The prefrontal cortex (PFC) is deeply involved in higher brain functions, many of which are altered in psychiatric conditions. The PFC exerts a top-down control of most cortical and subcortical areas through descending pathways and is densely innervated by axons emerging from the brainstem monoamine cell groups, namely, the dorsal and median raphe nuclei (DR and MnR, respectively), the ventral tegmental area and the locus coeruleus (LC). In turn, the activity of these cell groups is tightly controlled by afferent pathways arising from layer V PFC pyramidal neurons. The reciprocal connectivity between PFC and monoamine cell groups is of interest to study the pathophysiology and treatment of severe psychiatric disorders, such as major depression and schizophrenia, inasmuch as antidepressant and antipsychotic drugs target monoamine receptors/transporters expressed in these areas. Here we review previous reports examining the presence of monoamine receptors in pyramidal and GABAergic neurons of the PFC using double in situ hybridization. Additionally, we present new data on the quantitative layer distribution (layers I, II–III, V, and VI) of monoamine receptor-expressing cells in the cingulate (Cg), prelimbic (PrL) and infralimbic (IL) subfields of the medial PFC (mPFC). The receptors examined include serotonin 5-HT1A, 5-HT2A, 5-HT2C, and 5-HT3, dopamine D1 and D2 receptors, and α1A-, α1B-, and α1D-adrenoceptors. With the exception of 5-HT3 receptors, selectively expressed by layers I–III GABA interneurons, the rest of monoamine receptors are widely expressed by pyramidal and GABAergic neurons in intermediate and deep layers of mPFC (5-HT2C receptors are also expressed in layer I). This complex distribution suggests that monoamines may modulate the communications between PFC and cortical/subcortical areas through the activation of receptors expressed by neurons in intermediate (e.g., 5-HT1A, 5-HT2A, α1D-adrenoceptors, dopamine D1 receptors) and deep layers (e.g., 5-HT1A, 5-HT2A, α1A-adrenoceptors, dopamine D2 receptors), respectively. Overall, these data provide a detailed framework to better understand the role of monoamines in the processing of cognitive and emotional signals by the PFC. Likewise, they may be helpful to characterize brain circuits relevant for the therapeutic action of antidepressant and antipsychotic drugs and to improve their therapeutic action, overcoming the limitations of current drugs.